Biochemical and molecular properties of LHCX1, the essential regulator of dynamic photoprotection in diatoms. Issue 1 (7th September 2021) - Giovagnetti, Vasco; Jaubert, Marianne; Shukla, Mahendra K; Ungerer, Petra; Bouly, Jean-Pierre; Falciatore, Angela; Ruban, Alexander V
Abstract: Light harvesting is regulated by a process triggered by the acidification of the thylakoid lumen, known as nonphotochemical "energy-dependent quenching" (qE). In diatoms, qE is controlled by the light-harvesting complex (LHC) protein LHCX1, while the LHC stress-related (LHCSR) and photosystem II subunit S proteins are essential for green algae and plants, respectively. Here, we report a biochemical and molecular characterization of LHCX1 to investigate its role in qE. We found that, when grown under intermittent light, Phaeodactylum tricornutum forms very large qE, due to LHCX1 constitutive upregulation. This "super qE" is abolished in LHCX1 knockout mutants. Biochemical and spectroscopic analyses of LHCX1 reveal that this protein might differ in the character of binding pigments relative to the major pool of light-harvesting antenna proteins. The possibility of transient pigment binding or not binding pigments at all is discussed. Targeted mutagenesis of putative protonatable residues (D95 and E205) in transgenic P. tricornutum lines does not alter qE capacity, showing that they are not involved in sensing lumen pH, differently from residues conserved in LHCSR3. Our results suggest functional divergence between LHCX1 and LHCSR3 in qE modulation. We propose that LHCX1 evolved independently to facilitate dynamic tracking of light fluctuations in turbulent waters. The evolution of LHCX(-like) proteins in organisms with secondary red plastids, such as diatoms, might have conferred a selective advantage in the control of dynamic photoprotection, ultimately resulting in their ecological success. Abstract : The protein LHCX1 evolved in diatoms to facilitate dynamic photoprotection without being the quenching site.